Coupling driving factors of eco-environmental protection and high-quality development in the yellow river basin - Xin, Yun; Liu, Xiaoyu (Frontiers in Environmental Science, 2022)
Most cities in the Yellow River Basin are located in the central and western regions of China. Restricted by historical evolution, natural environment, resource endowments and other conditions, the economic and social development model of the Yellow River Basin region is outdated, and the level of economic and social development is relatively lagging, which hinders its coordinated development of ecology and economy. This paper uses the coupling coordination degree model, GIS spatial analysis method, NAR neural network model, spatial autoregression, and geographically weighted regression model to investigate the coupling coordination level, spatial differentiation characteristics, future development trend, and coupling driving factors of eco-environmental protection and high-quality development in the Yellow River Basin. The results show that From 2003 to 2018, the level of eco-environmental protection and high-quality development in most areas of the Yellow River Basin gradually improved, presenting a spatial imbalance characteristic of “high in the east and low in the west. The coupling coordination degree of eco-environmental protection and high-quality development in various regions of the Yellow River Basin increased year by year during the survey period. In 2018, most cities had been transformed into intermediate coordinated development areas, and most cities in Inner Mongolia and the middle and lower reaches south of the Yellow River have been upgraded to a well-coordinated development stage. The coupled and coordinated development relationship between eco-environmental protection and high-quality development in the Yellow River Basin has significant spatial agglomeration characteristics, and the local spatial positive correlation gradually increases. From 2019 to 2023, the average level of coupling coordination between eco-environmental protection and high-quality development in the Yellow River Basin during the forecast period is 0.802, 0.807, 0.809, 0.813, and 0.816, respectively, all of which have entered a stage of well-coordinated development. The coupled driving factors of ecological protection and high-quality development in the Yellow River Basin are ranked from strong to weak: energy utilization, urbanization, water resources development, and industrialization. Among them, the degree of energy utilization is the root of the differentiation of coupling coordination between eco-environmental protection and high-quality development in 74 regions of the Yellow River Basin. This study puts forward two strategic suggestions based on the optimal utilization strategy of energy and water resources and the coordinated promotion strategy of industrialization and urbanization, which has great practical and scientific significance for promoting the coordinated development of ecological environment protection and high-quality development in the Yellow River Basin.